Bowl‐shaped Cluster CuB12−: A Viable Global Minimum with Twofold Aromaticity. Issue 19 (19th July 2022) - Solar‐Encinas, José; Leyva‐Parra, Luis; Yáñez, Osvaldo; Inostroza, Diego; Barrios‐Llacuachaqui, Julio R.; Vásquez‐Espinal, Alejandro; Orellana, Walter; Tiznado, William
Abstract: A low‐lying structure is revealed for the CuB12 − cluster, which is bowl‐shaped. It consists of a triangular CuB2 base and a B10 rim. Molecular dynamics simulations indicates its structural robustness; at an elevated temperature (600 K), the base rotates reversibly within the B10 perimeter. Chemical bonding analysis detects 2σ‐ and 3π‐delocalized bonds, suggesting double aromaticity. This is also confirmed by two diatropic and concentric ring currents under an external magnetic field. Abstract : The doubly aromatic global minimum bowl‐shaped structure of the CuB12 − cluster is revealed by DFT and ab‐initio calculations.